2006
DOI: 10.1080/09650790600847636
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and reflexivity in feminised education action research

Abstract: The paper addresses contemporary relations between emotions, gender and feminist action research. Starting from analysis of the increasing emotionalisation of everyday life, it explores the quasi-feminist-or what the author calls 'feminised'-forms of incitement to reflexive confession that are increasingly gaining favour within professional and higher educational contexts and draws on literatures and sets of debates that inform education action research, including: childhood and governmentality; feminist resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
1
32
0
1
Order By: Relevance
“…In education or in management learning activities (and also in qualitative research), we are more and more invited to talk and write about emotion. Emotions thus become textualised through writing (and the reading and interpretation of those writing)s. We have to exercise extreme caution toward this form of emotional literacy, however, since it risks becoming a new form of regulatory discourse that disciplines the expression of emotions precisely when we try to give voice to them (Burman, 2006;.…”
Section: Learning Emotionsmentioning
confidence: 99%
“…In education or in management learning activities (and also in qualitative research), we are more and more invited to talk and write about emotion. Emotions thus become textualised through writing (and the reading and interpretation of those writing)s. We have to exercise extreme caution toward this form of emotional literacy, however, since it risks becoming a new form of regulatory discourse that disciplines the expression of emotions precisely when we try to give voice to them (Burman, 2006;.…”
Section: Learning Emotionsmentioning
confidence: 99%
“…The research reported in this paper is informed by narrative methodology (Bruner, 1991(Bruner, , 1986Clandinin & Rosiek, 2007;Heikkinen, 2002;Lieblich, 2003;Pinnegar & Daynes, 2007) and reflexive orientation (Alvesson & Sköldberg, 2009;Burman, 2006;Davies, 1999;Denzin & Lincoln, 1998;Rallis, 2010;Skeggs, 2002). In this kind of research the concept of "data" tends not to apply, or its application tends to be problematic.…”
Section: Data and Analysismentioning
confidence: 98%
“…A ello se suman otras dos razones sobre la importancia de las emociones en investigación acción educativa feminista, tal como plantea Burman (2006), por un lado, la implicación de las emociones en la cuestión de la participación; por otro, la consideración de las emociones como formas de acción en la investigación. Burman (2006) parte de dos supuestos: la 'emocionalización' de la vida pública y la entrada de ello en las prácticas educativas. Utiliza el término «geografías emocionales» para destacar la dimensión relacional de las emociones y afirma que la reflexividad, en tanto que práctica educativa e investigadora, configura el espacio para la participación.…”
Section: Sujeto Valores Y Emociones En La Investigación Social Feminunclassified